2012
DOI: 10.1016/j.neurobiolaging.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index is associated with biological CSF markers of core brain pathology of Alzheimer's disease

Abstract: Weight changes are common in aging and Alzheimer’s disease (AD) and post-mortem findings suggested a relation between lower body mass index (BMI) and increased AD brain pathology. In the current multicenter study, we tested whether lower BMI is associated with higher core AD brain pathology as assessed by cerebrospinal fluid (CSF) based biological markers of AD in 751 living subjects: 308 patients with AD, 296 subjects with amnestic mild cognitive impairment (MCI), and 147 elderly healthy controls (HC). Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 50 publications
6
40
2
Order By: Relevance
“…The NC and MCI groups had significantly higher MMSE scores compared to those of the AD group. The mean body mass index (BMI) was lower in MCI and AD cohorts, significantly so for the latter compared to NC (Table 1), as reported previously [29]. Baseline plasma leptin values were significantly lower in the MCI group, compared to NC and while lower in the AD subjects, values were not significantly different from MCI subjects (Table 1), in agreement with previous studies [16, 17, 30].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The NC and MCI groups had significantly higher MMSE scores compared to those of the AD group. The mean body mass index (BMI) was lower in MCI and AD cohorts, significantly so for the latter compared to NC (Table 1), as reported previously [29]. Baseline plasma leptin values were significantly lower in the MCI group, compared to NC and while lower in the AD subjects, values were not significantly different from MCI subjects (Table 1), in agreement with previous studies [16, 17, 30].…”
Section: Resultssupporting
confidence: 90%
“…Our cross-sectional observations imply that plasma leptin levels in MCI men and possibly non-obese women are different to those predicted by BMI values in NC. Thus, leptin as a marker could strengthen the predictive power of low BMI which has been consistently linked to disease onset [29, 35, 36], and associated with biological markers of core brain pathology of AD [29]. The present data suggest but do not prove that for both genders, the decline in circulating leptin itself may have a role in the cascade of AD causation.…”
Section: Discussionmentioning
confidence: 52%
“…A cross-sectional study found that abnormal CSF levels of Ab 42 and tau were associated with lower body mass index in a sample comprising individuals with and without memory problems (i.e., were cognitively normal, had MCI, or had AD dementia), 20 consistent with a possible link between abnormal AD biomarker levels and weight loss. A literature review did not reveal any prior studies that examined biomarkers as a predictor of future weight loss among cognitively normal individuals.…”
mentioning
confidence: 88%
“…The appreciation that AD pathology develops decades prior to the initial cognitive symptoms suggest that the late-life changes in body weight may reflect the earliest stage of the disease process [40,46]. Supporting this notion, low BMI is associated with worsening AD pathology in postmortem brains [47,48] as well as worsening CSF biomarkers (tau and Aβ1–42) [49]. Collectively, these studies suggest that increased adiposity during midlife contribute or influence the risk of developing age-related dementia, while reduced adiposity in late-life is an early consequence of the disease and may contribute to its progression.…”
Section: Body Weight/adiposity In Normal Aging and Age-related Dementiamentioning
confidence: 99%